The effects of VAR interventions on self-rated mental fatigue and self-rated performance of football referees - Samuel, R. D.; Englert, C.; Basevitch, I.; Galily, Y. (International Journal of Performance Analysis in Sport, 2024)
Football referees are required to make numerous decisions per match under physiological and emotional strain. Within this context, VAR (video assistant referee) interventions represent a key match event in which referees` critical decisions are challenged and thus their perceived ability to control the match might also be obscured. In this study, we investigated the effects of a VAR intervention on referees` self-rated mental fatigue (MF) and performance. Nine elite referees completed over 2-6 real matches each (total of 44 matches) a single item of MF before the match, at half-time, and immediately after the match. Situational and performance indices were also collected. The referees` level of MF significantly increased from pre-match to half-time to post-match, yet the referees were not completely mentally fatigued at the end of the matches. Post-match MF was higher (a medium effect) for matches with a VAR intervention (n = 9) compared with matches without an intervention (n = 35). Post-match MF correlated negatively with self-rated performance, r(44) = .35, p = .019. These findings are discussed in relation to current theory and research in the area of self-control and MF in sports. We also provide recommendations for referee training and match preparation.